Awareness Nazir Cash Waqf Registered in the Agency West Sumatra Waqf Against Management Risk - Ria Anjani; Mohamad Fany Al Farisi; Rida Rahim (Institute of Computer Science (IOCS), 2022)
This study aims to find out how Nazir's awareness registered with BWI (Indonesian Waqf Board) West Sumatra Region towards cash waqf risk management, knowing what risks exist in each institution and how to mitigate the risks that exist in the institution. The research method uses a mixed exploratory method, preceded by structured interviews and then filling out online questionnaires. The results of the study show that overall nazir registered with BWI West Sumatra Region has an awareness of the risks of cash waqf management, the risks contained in the institution consist of financial risk, operational risk, sharia non-compliance risk and reputation risk. Risk mitigation carried out includes investing cash waqf in the form of deposits, investing in own products, making soup (standard operating procedures), having a DSN-MUI certified supervisory board, fulfilling the mandate of wakif, transacting only with Islamic banks, making certificates as nazir who registered with BWI, conducting socialization about cash waqf, reporting and commitment to be willing to be audited and others. With the small number of cash waqf owned by some of these money waqf nazir institutions, it indicates that the public's interest and knowledge of cash waqf is still low. Whereas West Sumatra is an area with a Muslim majority, which should have good knowledge and literacy regarding cash waqf.